Comparative Analysis of Economic Growth in Countries Implementing Conventional Versus Islamic Financial Systems - Firdaus, Firdaus; Ilham, Muhammad; Asiam, Siti; Nurbaiti, Nurbaiti; Nasution, Yenni Samri Juliati (Talaa : Journal of Islamic Finance, 2024)
This research is motivated by the global economic growth that moves volatile and the vulnerability of the conventional financial system to the recession that hit the last few decades and the Islamic financial system that is still not well implemented in Muslim-majority countries. This study analyzes the comparison of economic growth for countries that implement Islamic and conventional financial systems. The sample is 10 countries with the largest Islamic financial assets and 10 largest countries that implement conventional financial systems. Independent t-test/Mann Whitney test is used for hypothesis testing. The results of this study show that there is no difference in economic growth for countries that apply Islamic and conventional financial systems. This is due to the relatively small size of the Islamic financial ecosystem and its incomplete implementataion in many Muslim-majority countries.